2008
DOI: 10.1080/15257770802138558
|View full text |Cite
|
Sign up to set email alerts
|

Uric Acid: The Oxidant-Antioxidant Paradox

Abstract: Uric acid, despite being a major antioxidant in the human plasma, both correlates and predicts development of obesity, hypertension, and cardiovascular disease, conditions associated with oxidative stress. While one explanation for this paradox could be that a rise in uric acid represents an attempted protective response by the host, we review the evidence that uric acid may function either as an antioxidant (primarily in plasma) or pro-oxidant (primarily within the cell). We suggest that it is the pro-oxidati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
549
1
21

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 724 publications
(610 citation statements)
references
References 61 publications
9
549
1
21
Order By: Relevance
“…Cardiovascular disease (CVD) is the leading cause of death in the older population, and the prevalence and incidence of CVD increases exponentially with advancing age 2. Uric acid, the final product of purine degradation in humans, mediates proinflammatory endothelial dysfunction and is associated with greater risks for CVD events 3, 4. Although a wealth of research has reported that an elevated serum uric acid (SUA) level >7 mg/dL independently predicts all‐cause and CVD‐related mortality in middle‐aged adults,5, 6, 7 studies linking hyperuricemia to mortality risks in the elderly population are conflicting and inconclusive 8, 9, 10, 11, 12, 13, 14.…”
mentioning
confidence: 99%
“…Cardiovascular disease (CVD) is the leading cause of death in the older population, and the prevalence and incidence of CVD increases exponentially with advancing age 2. Uric acid, the final product of purine degradation in humans, mediates proinflammatory endothelial dysfunction and is associated with greater risks for CVD events 3, 4. Although a wealth of research has reported that an elevated serum uric acid (SUA) level >7 mg/dL independently predicts all‐cause and CVD‐related mortality in middle‐aged adults,5, 6, 7 studies linking hyperuricemia to mortality risks in the elderly population are conflicting and inconclusive 8, 9, 10, 11, 12, 13, 14.…”
mentioning
confidence: 99%
“…Erythrocytes-reduced glutathione is one of the major non-enzymatic endogenous antioxidants protecting tissue against ROS. [9,22] Other antioxidants are alphatocopherol [23,24] , uric acid [25][26][27] , ascorbic acid [28] , carotenoids [29,30] and varieties of plant secondary metabolites such as flavonoid and related polyphenolic compounds. [31,32] Notable erythrocyte enzymatic ROS scavenging systems include glutathione reductase, [17,19] glutathione peroxidase, [33] glucose-6-phosphate dehydrogenase, [18,34] superoxide dismutase, [5,35] catalases, [36][37][38] peroxiredoxins, [39,40] and NADHmethaemoglobin reductase.…”
Section: Introductionmentioning
confidence: 99%
“…In the last years a paradoxal role of uric acid has been hypothesized as it could act as an antioxidant in plasma and extracellular environment and as a pro-oxidant within the cells [40,42]; it is not possible to exclude that MS subjects with type 2 diabetes mellitus were hyperuricemic but we know the serum uric acid levels of a small group of MS subjects (data not shown).…”
Section: Discussionmentioning
confidence: 99%